On Veronica paczoskiana and the real identity and typification of V. spicata var. pseudoorchidea (Plantaginaceae) - Mosyakin, Sergei L.; Albach, Dirk C.; Shevera, Myroslav V. (Phytotaxa, 2023)
Our critical re-assessment of the relevant publications by Paczoski and other available literature demonstrated that the name Veronica spicata var. pseudoorchidea was validly published, with a rather detailed descriptive statement and discussion, not in 1910 (in that Paczoski’s book, this variety was briefly discussed but not named) and not from southern Ukraine (as it was suggested by Klokov in 1976, and in several publications by other authors), but in 1909 in Paczoski’s article on the flora and vegetation of the area near the Motovylivka railway station, now in Fastiv District of Kyiv Region, located at the border of the northern Forest Zone (Polissya, Polesie) and the Forest-Steppe Zone of Ukraine. In that article Paczoski, in particular, mentioned that his plant specimens collected in that area are deposited in the herbarium of the Kherson Regional Museum (Kherson, Ukraine). The study of two original specimens of V. spicata var. pseudoorchidea (syntypes, of which one is here designated as the lectotype) in the herbarium of Paczoski held at the Museum clearly demonstrated that the morphological characters of these plants perfectly correspond to the characters indicated by Klokov for his supposedly distinct taxon, V. paczoskiana (described from the Mykhaylivka Forest near Kaniv, Cherkasy Region, Ukraine), and the syntypes of V. spicata var. pseudoorchidea do not differ from the holotype and other original specimens of V. paczoskiana at KW. Thus, if accepted as a variety, the glabrous or sparsely pubescent plants growing mainly in pine forests of Ukraine, Belarus, partly also in the European part of Russia and Siberia should be called V. spicata var. pseudoorchidea. If such plants were accepted at a species or subspecies rank, their correct names would be V. paczoskiana or V. spicata subsp. paczoskiana, respectively. Based on analyses of DNA polymorphisms and morphological data (analyzed separately), we prefer the rank of variety.